A pyroptosis-related lncRNA signature in bladder cancer - Wang,P; Wang,Z; Zhu,L; Sun,Y; Castellano,L; Stebbing,J; Yu,Z; Peng,L (Cancer Medicine, 2023)
PurposePyroptosis, a type of programmed cell death, is implicated in the tumorigenesis, development and migration of cancer, which can be regulated by long non-coding RNAs (lncRNAs). Our research aimed to investigate the prognostic role of pyroptosis-related lncRNAs and the relationship to the tumor immune microenvironment through bioinformatics analysis.MethodsThe clinical and RNA-sequencing data of bladder cancer patients were downloaded from The Cancer Genome Atlas (TCGA). And 412 bladder cancer subjects with clinical information were divided into training and testing cohort. And 52 reported pyroptosis-related genes were used to screen pyroptosis-related lncRNAs. A pyroptosis-related lncRNA signature was constructed based on Cox regression analyses.ResultsA 9-pyroptosis-related-lncRNA signature was identified to separate patients with bladder cancer into two groups. The prognosis of bladder cancer patients in the high-risk group was significantly inferior compared with those in the low-risk group. Risk scores were validated to develop an independent prognostic indicator based on multivariate Cox regression analysis. Receiver operating characteristic curve (ROC) analysis examined the signature on overall survival. The area under time-dependent ROC curve (AUC) at 1-, 3, and 5-years measured 0.747, 0.783, and 0.768, respectively. Analysis of the immune landscape and PD-L1 expression showed that PD-L1 is upregulated in the high-risk group. The immunocyte subtypes of the two groups were different.ConclusionA novel pyroptosis-related lncRNA signature was identified with prognostic value for bladder cancer patients. Pyroptosis-related lncRNAs have a potential role in cancer immunology and may serve as prognostic or therapeutic targets.